1, 25‐Dihydroxy vitamin D prevents tumorigenesis by inhibiting oxidative stress and inducing tumor cellular senescence in mice. Issue 2 (1st March 2018) - Chen, Lulu; Yang, Renlei; Qiao, Wanxin; Yuan, Xiaoqin; Wang, Shui; Goltzman, David; Miao, Dengshun
Abstract : Human epidemiological studies suggest that 1, 25(OH)2 D3 deficiency might increase cancer incidence, but no spontaneous tumors have been reported in mice lacking 1, 25(OH)2 D3 or deficient in its receptor. In our study, we detected, for the first time, diverse types of spontaneous tumors in l, 25(OH)2 D3 deficient mice more than 1 year of age. This was associated with increased oxidative stress, cellular senescence and senescence‐associated secretory phenotype molecules, such as hepatocyte growth factor, mediated via its receptor c‐Met. Furthermore, 1, 25(OH)2 D3 prevented spontaneous tumor development. We also demonstrated that l, 25(OH)2 D3 deficiency accelerates allograft tumor initiation and growth by increasing oxidative stress and DNA damage, activating oncogenes, inactivating tumor suppressor genes, stimulating malignant cell proliferation and inhibiting their senescence; in contrast, supplementation with exogenous l, 25(OH)2 D3 or antioxidant, or knock‐down of the Bmi1 or c‐Met oncogene, largely rescued the phenotypes of allograft tumors. Results from our study suggest that 1, 25(OH)2 D3 deficiency enhances tumorigenesis by increasing malignant cell oxidative stress and DNA damage, stimulating microenvironmental cell senescence and a senescence‐associated secretory phenotype, and activating oncogenes and inactivating tumor suppressor genes, thus increasing malignant cell proliferation. Our study provides direct evidence supporting the role of vitamin D deficiency in increasing cancer incidence. Conversely, 1, 25(OH)2 D3 prevented spontaneous tumor development, suggesting that this inhibitory effect prevents the initiation and progression of tumorigenesis, thus provides a mechanistic basis for 1, 25(OH)2 D3 to prevent tumorigenesis in an aging organism. Abstract : What's new? Vitamin D (l, 25(OH)2 D3 ) is thought to play a role in lowering cancer incidence. However, associations between cancer and l, 25(OH)2 D3 sufficiency or deficiency are unclear. In this study, diverse types of spontaneous tumors were detected in aged l, 25(OH)2 D3 ‐deficient mice. In addition, l, 25(OH)2 D3 deficiency was found to accelerate allograft tumor initiation and growth by elevating oxidative stress, by stimulating microenvironmental cell senescence, and by activating oncogenes and inactivating tumor suppressor genes. These effects resulted in increased malignant cell proliferation and inhibition of tumor cellular senescence. By contrast, l, 25(OH)2 D3 supplementation in deficient mice blocked spontaneous tumor development and rescued allograft tumor phenotypes.